2020
DOI: 10.1007/s00221-019-05711-y
|View full text |Cite
|
Sign up to set email alerts
|

Visual cues, expectations, and sensorimotor memories in the prediction and perception of object dynamics during manipulation

Abstract: When we grasp and lift novel objects, we rely on visual cues and sensorimotor memories to predictively scale our finger forces and exert compensatory torques according to object properties. Recently, it was shown that object appearance, previous force scaling errors, and previous torque compensation errors strongly impact our percept. However, the influence of visual geometric cues on the perception of object torques and weights in a grasp to lift task is poorly understood. Moreover, little is known about how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Previous research has demonstrated that implicit learning of the underlying dynamics can be beneficial for sampling, for instance through haptic exploration 35 . In addition, implicit sensorimotor memories of object properties can influence the anticipation of these properties 36 , both in the absence and presence of explicit cues 37 . Yet our kinematic results did not reveal any benefit from the explicit instruction about the trial sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that implicit learning of the underlying dynamics can be beneficial for sampling, for instance through haptic exploration 35 . In addition, implicit sensorimotor memories of object properties can influence the anticipation of these properties 36 , both in the absence and presence of explicit cues 37 . Yet our kinematic results did not reveal any benefit from the explicit instruction about the trial sequence.…”
Section: Discussionmentioning
confidence: 99%
“…The findings reveal a neural substrate that enable humans to predictively and adaptively manipulate objects with dynamically fluctuating properties. These substrates may vary depending on the availability of visual cues 30 and depending on more static object properties (e.g. weight).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to prehensile tasks aiming at stabilizing the object relative to the hand, manipulation requires the ability to move and rotate the object relative to the body, and supports the use of tools for actions on the environment. Manipulation imposes greater challenges to the sensorimotor system than grasping, including the anticipation of inertial forces and torques in response to variations in the position and orientation of the handheld object ( Schneider et al, 2020 ). In-hand manipulation implies a particularly sophisticated form of manual dexterity where independent finger movements enable the displacement of the object with respect to the hand ( Elliott and Connolly, 1984 ).…”
Section: Naturalistic Activity: Compensatory Strategies To Ensure Task Completionmentioning
confidence: 99%